Investigating the status of the second victims of error and related factors in nurses: a description study - Fardin Shahbazzadeh; Aghil Habibi Soola; Sajjad Narimani; Mehdi Ajri-Khameslou (BMC Nursing)
Abstract Background Errors not only affect patients as the primary victim but also have a negative impact on nurses as the secondary victim; therefore, understanding the reasons for the second victim’s error, as well as the elements that contribute to this phenomenon, is critical for managing the mistake. The main purpose of this research was to determine the status of second victims of error and related factors in nurses. Methods This is an analytical-descriptive study conducted in Iran. The study’s statistical population comprised all nurses working in the five teaching hospitals of Ardabil city. A random sampling method was used. The data collection tool included a demographic characteristics questionnaire, a questionnaire on previous nursing error experience characteristics, and the Second Victim Experience and Support Tool. The collected data was analyzed in SPSS-16 software. Results The results obtained from this research showed that the average score of second victims of error among nurses participating in the study was 85.89 (10/17). Based on the results obtained, there was a significant relationship between the number of second victims of error phenomena with age (p < 0.01 and r = -0.179) and work experience (p < 0.01 and r = -0.156), the number of cases of errors in 12 previous months, having an error that resulted in injury in the last 12 months, the history of going to court, the way nursing errors were reported, and the way managers dealt with nurses’ errors (p < 0.05). Conclusions The nurses under study had an average level of the phenomenon of second victims of error, and a set of individual and organizational factors were influential in the development of this phenomenon. The second victim of error phenomenon was more prevalent among novice nurses, who tended to make more mistakes in a reprimanding work environment. Therefore, it is recommended that hospitals use a justice-oriented policy instead of a reprimand policy against nursing errors.